Gender discourse in Kitab al-Tabaqat al-Kubra: deconstructing Ibn Sa'd's portrayal of the model Muslim woman - Abou-Taleb, Amira Naim (AUC Knowledge Fountain, 2012)
This study examines the impact of Ibn Saʽd’s (d. 230/845) historical context on his portrayal of the women of the Prohetic household in Kitab al-Tabaqat al-Kubra (KTK). The KTK stands as the oldest, extant version of a biographical dictionary of the early Muslim community and has been canonized as an authority on the lives of individuals who are perceived as the exemplary model (al-salaf al-ṣaliḥ) for later Muslims generations. As critical historiography suggests a strong link between a historical narrative and the socio-political context in which it was created, the two hundred year gap between the time of authorship of the KTK and the period which it narrates could have had a significant impact on the author’s discourse. Especially that the work was authored during the vibrant ʽAbbasid period of Harun al-Rashid and al-Maʾmun ; a time that witnessed the production of the Sunni intellectual narratives of hadith collections, schools of jurisprudence (fiqh), as well as major historical annals. Gender representation is a particularly intriguing area of examination; therefore, this study identifies and analyzes main themes and topoi in Ibn Saʽd’s portrayal of prominent women (the Prophet’s wives and daughters) in relation to the local traditions in Iraq and developing fiqh legislation. The themes are compared to Ibn Sa’d’s presentation of other “common” women as well as to prominent men and gauged against biographical works by other authors to assess how such women were presented differently. The findings echo the fusion of sira, hadith, and local regional traditions which, combined, present the tenets of a power discourse advancing the call of a patriarchal ʽAbbasid Imperial project as the guardian of the Sunni doctrine of the time.